Influência da estação do ano, estádio de lactação e da hora da ordenha sobre o número de células somáticas do leite bovino - Vasconcelos, CGC; Nader, A.; Amaral, L. A.; Pereira, G. T. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1997)
From January to October of 1995, somatic cell countings were accomplished in 2,218 milk samples collected from 67 quarters of 17 lactating cows at the initial, middle and final stages of lactation, in the morning and evening milkings. The highest means of cell countings were observed among the milk samples collected at the Final stage of lactation 15.652cell/ml), in the winter (5.358cell/ml) and the afternoon milking (5.199cell/ml). The differences observed amongst the cell countings in samples obtained at the different stages of lactation and the morning and afternoon milkings were statistically significant (P < 0.0001). In contrast differences observed amongst the seasons of the year, showed to be non-significant at the level of 5% probability. Higher occurrence of samples with cell countings superior to 500,000cell/ml was verified at the final stage of lactation (34.9%), in the winter (23.6%) and the afternoon milking (21.3%). These findings show the influence of physiologic and management factors (stage of Lactation and milking time) on milk cell concentrations.
Influence of the season of the the year, stage of lactation and milking time on somatic cell counts in bovine milk
Keywords: Bovine; stage of lactation; season of the year; Somatic cell